Nectin-1 and Non-muscle Myosin Heavy Chain-IIB: Major Mediators of Herpes Simplex Virus-1 Entry Into Corneal Nerves - Wang, Chenchen; Liang, Qi; Sun, Dong; He, Yun; Jiang, Jiaxuan; Guo, Rongjie; Malla, Tejsu; Hamrah, Pedram; Liu, Xun; Huang, Zhenping; Hu, Kai (Frontiers in Microbiology, 2022)
Herpes Simplex Virus 1 (HSV-1) invades corneal nerves upon its infection of the cornea and then establishes latency in the trigeminal ganglion (TG). The latent virus in TG is often reactivated and travels back to the cornea, causing recurrent herpes simplex keratitis (HSK). The entry of HSV-1 into the corneal nerve is considered the initial step of infection resulting in HSV-1 latency and HSK recurrence. Several gD and gB receptors have been identified, including nectin-1, herpes virus entry medium (HVEM) and 3-O-sulfated heparan sulfate (3-OS-HS) as gD receptors, and non-muscle myosin heavy chain IIA (NMHC-IIA), NMHC-IIB and myelin-associated glycoprotein (MAG) as gB receptors. However, which receptors contribute to the entry of HSV-1 into corneal nerves are yet to be determined. This study observed that receptors nectin-1, HVEM, 3-OS-HS, NMHC-IIA, and NMHC-IIB, not MAG, were expressed in healthy corneal nerves. Further, we cultured TG neurons extracted from mice in vitro to screen for functional gD/gB receptors. Both in vitro siRNA knockdown and in vivo antibody blocking of either nectin-1 or NMHC-IIB reduced the entry and the replication of HSV-1 as shown by qPCR analysis and immunofluorescence measure, respectively. Also, we observed that the re-localization and the upregulation expression of NMHC-IIB after HSV-1 exposure were inhibited when gD receptor nectin-1 was knocked down. These data suggest that nectin-1 was the main gD receptor and NMHC-IIB was the main gB receptor in mediating HSV-1 entry and hold promise as therapeutic targets for resolving HSV-1 latency and HSK recurrence.